2021
DOI: 10.3389/fsurg.2021.721770
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Vulvar Flap Viability Evaluation With Near-Infrared Probe and Indocyanine Green for Vulvar Cancer Reconstructive Surgery: A Feasible Technique

Abstract: Introduction: Vulvar cancer is a rare condition affecting older women and accounts for 3–5% of all gynecological cancers. Primary surgical treatment involves the removal of a large amount of tissue for which reconstructive surgery is often necessary with a high rate of postoperative complications. Despite several techniques for the evaluation of vulvar flap viability have been proposed, many methods cannot be performed during surgery and require expensive devices often missing in a gynecological clinic. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the initial stages of vulvar, only surgery is considered as the backbone of treatment, whereas in advanced stages, surgery is combined with chemotherapy or radiation (128)(129)(130). Surgical intervention ensures adequate local control, but it comes with anatomical or functional limitations that compromise quality of life and sexual function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stages of vulvar, only surgery is considered as the backbone of treatment, whereas in advanced stages, surgery is combined with chemotherapy or radiation (128)(129)(130). Surgical intervention ensures adequate local control, but it comes with anatomical or functional limitations that compromise quality of life and sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…With V-Y fasciocutaneous flap repair, Hand et al found 33 and 15% surgical dehiscence and infection, respectively (138). The vitality of the restored tissue following its displacement is an important factor in vulvar flap success (128). Some points about reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to VEIL-H, it can be a safe surgical approach with more minimally invasion. For those with a larger scope of vulvar excision, the reconstructive techniques of the perineum after radical surgery, alongside VEIL-V, could increase the quality of life of these patients ( 20 , 21 ). Since the choice of incision is located 2 cm from the outer edge of the tumor, this surgical method is not suitable for tumors close to the perineal union, which will cause inconvenience in operation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, regarding wether reconstructive surgery should be performed. Generally, for vulvar caner, surgeons always aim for surgical margins of 2 cm to achieve pathological margins of at least 8 mm to minimize local disease recurrence, removing a large amount of tissue ( 11 ).In these circumstances, reconstructive surgery is often necessary, after radical wide local excision of tumor or radical vulvectomy, to reduce the risk of postoperative complication ( 12 15 ). Female cellular angiofibroma predominantly occurs in the superficial soft tissues of the vulva ( 2 ).…”
Section: Discussionmentioning
confidence: 99%